Post-COVID-19 paradoxical vocal cord movement and dysfunctional dysphonia: A clinical case - Antoine El Kik; Hind Eid; Zeina Aoun Bacha (Respiratory Medicine Case Reports, 2022)
Introduction: Post-COVID persistent dyspnea linked to a paradoxical vocal fold movement has rarely been described, and it has never been described as associated with dysfunctional dysphonia. Case study: We present a case of a 46-year-old patient with severe COVID-19 history who presented to our hospital for persistent cough, dysphonia, and intermittent episodes of dyspnea, getting worse when speaking. A chest computed tomography (CT) scan done was normal. The patient was treated by empiric bronchodilators with inhaled corticosteroids but without any improvement. A bronchoscopy was done and revealed spontaneous paradoxical vocal fold movement and dysfunctional dysphonia. The patient was referred to a speech therapist, and her problem was resolved. Conclusion: Resistant dyspnea to empiric treatment, after COVID-19, should suggest the diagnosis of paradoxical vocal fold movement. Laryngoscopy should be done to confirm the diagnosis, and the patient should be referred to a speech therapist.